CSPL: An Ada95-like, unix-based process environment - Chen, JYJ (My University, 1997)
This paper presents a new process-centered environment called ''concurrent software process language'' (CSPL). CSPL takes a unique and innovative approach to integrate the object-oriented Ada95-like syntax (for its modeling power) with Unix shell semantics (for its enactment capability) in a software process language. This paper depicts the following new CSPL features: 1) object orientation, 2) multirole and multiuser, and 3) unified object modeling. Language constructs specially designed for software process such as work assignment statement, communication-related statements, role unit, tool unit, relation unit and so on, are, respectively, described. The related work of this diversified field is also surveyed in some depth. The CSPL environment prototype has been built. A CSPL process program for the IEEE Software Process Modeling Example Problem has been developed and enacted to demonstrate the capabilities of this environment.
Keywords: process-centered environment; software process; software engineering; software engineering environment; process modeling